Effective efficiency and power density analysis for WiDE as a fuel in diesel engine performance - Rai R.K.; Sahoo R.R. (My University, 2025)
A comparative theoretical performance analysis for diesel, 5% water in diesel emulsion (WiDE), and 10% WiDE as fuels in a single-cylinder diesel engine is presented here. Variations in engine performance parameters such as effective power density (EPD), effective power (EP), and effective efficiency (EE), along with compression ratio and equivalence ratio, have been analyzed on the basis of isobaric heat addition and isochoric heat rejection assumptions. Also, friction loss, exhaust loss, and total loss occurring in engines with the above-mentioned fuels have been discussed. Theoretical analysis revealed that in a diesel engine with compression ratio 18, the EP and power density increased by 28.6% and 30.45%, respectively, for diesel fuel compared with 10% WiDE fuel. The optimum cycle temperature ratio, EP, and power density were obtained with an equivalence ratio of 1.2 and the optimum EE with an equivalence ratio of 0.89 for diesel, 5% WiDE, and 10% WiDE fuels. However, the maximum exhaust loss and the minimum incomplete combustion losses were obtained with an equivalence ratio of 1.2 and 0.8, respectively. At an equivalence ratio of 1.2, diesel fuel had a higher exhaust loss of 9.25% and 27.21% and heat loss of 5.39% and 11.8%, respectively, compared with 5% WiDE and 10% WiDE fuels. Thus, the fuel consumption rate with diesel as fuel was higher, followed by 5% WiDE and 10% WiDE fuels for diesel engine performance. © 2019 Wiley Periodicals, Inc.